2017
DOI: 10.1371/journal.pbio.2003318
|View full text |Cite
|
Sign up to set email alerts
|

Mutualism in museums: A model for engaging undergraduates in biodiversity science

Abstract: Museums have an untapped potential to engage students in hands-on learning. Here, we describe the development of a tiered museum-based program at the University of California, Berkeley as a model for engaging undergraduates in biodiversity science. This decade-long effort to increase student participation in collections demonstrates the mutual benefits of undergraduate involvement. Museums benefit from critical help in collections care and an increased intellectual vitality, while students simultaneously gain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The elevated profile of natural history museums as holders of biodiversity specimens and the digital data that represent them, in addition to interpretive kiosks and displays, has not been lost on undergraduate students, who themselves become outreach agents [118]. As museums reach out even more aggressively, exposing undergraduates to collections-based research and the incorporation of digital data in biodiversity science, the potential for downstream impacts, including recruitment of a more diverse constituency and a broader range of skill sets, will grow [119,120].…”
Section: Caveatsmentioning
confidence: 99%
“…The elevated profile of natural history museums as holders of biodiversity specimens and the digital data that represent them, in addition to interpretive kiosks and displays, has not been lost on undergraduate students, who themselves become outreach agents [118]. As museums reach out even more aggressively, exposing undergraduates to collections-based research and the incorporation of digital data in biodiversity science, the potential for downstream impacts, including recruitment of a more diverse constituency and a broader range of skill sets, will grow [119,120].…”
Section: Caveatsmentioning
confidence: 99%
“…Given the importance of museums as repositories of critical information about temporal and spatial patterns of biodiversity (Bradley et al, 2014;Suarez & Tsutsui, 2004), there is a growing need for trained professionals in natural history collections (Bradley et al, 2014). Natural history museums can help fill this growing need by providing training to undergraduates through hands-on research experiences, such as this project, and other immersive opportunities that can be formative in the careers of the next generation of researchers (Cook et al, 2014;Hiller et al, 2017;Powers et al, 2014;Russell et al, 2007). Furthermore, we consider science to be a community-driven enterprise and see the collection of DNA-quality topotypic materials and vouchers to be an opportunity for individuals and organizations to contribute to common resources that will facilitate current and future research efforts, and that these efforts can also serve as a platform to train undergraduate researchers.…”
Section: Resultsmentioning
confidence: 99%
“…Our inclusion of undergraduates offered them the opportunity for meaningful participation in a project addressing real-world issues related to biodiversity conservation and provided a connection and networking point to professional biologists (Hiller et al, 2017). Undergraduates were active participants in most aspects of the project and we found that undergraduates in the herpetology course at JMU benefitted from course-based research in several ways.…”
Section: Recommendations For Preparing Students To Lead Fieldworkmentioning
confidence: 96%
See 1 more Smart Citation
“…In North America, digitization efforts have been used to provide access to communities for whom collections have often been out of reach, providing opportunities to expand diversity in biodiversity conservation (Drew 2011). Multiple examples of directly integrating NHMs into undergraduate education have been developed which could serve as models for other countries (Cook et al 2014, Hiller et al 2017, Monfils et al 2017 as well as studies on the effectiveness of various education programs such as school tours (Cox-Petersen et al 2003).…”
Section: Biodiversity Educationmentioning
confidence: 99%